Moving beyond 'think leadership, think white male': the contents and contexts of equity, diversity and inclusion in physician leadership programmes. Issue 2 (19th April 2022) - Soklaridis, Sophie; Lin, Elizabeth; Black, Georgia; Paton, Morag; LeBlanc, Constance; Besa, Reena; MacLeod, Anna; Silver, Ivan; Whitehead, Cynthia Ruth; Kuper, Ayelet
Abstract : The lack of both women and physicians from groups under-represented in medicine (UIM) in leadership has become a growing concern in healthcare. Despite increasing recognition that diversity in physician leadership can lead to reduced health disparities, improved population health and increased innovation and creativity in organisations, progress toward this goal is slow. One strategy for increasing the number of women and UIM physician leaders has been to create professional development opportunities that include leadership training on equity, diversity and inclusivity (EDI). However, the extent to which these concepts are explored in physician leadership programming is not known. It is also not clear whether this EDI content challenges structural barriers that perpetuate the status quo of white male leadership. To explore these issues, we conducted an environmental scan by adapting Arksey and O'Malley's scoping review methodology to centre on three questions: How is EDI currently presented in physician leadership programming? How have these programmes been evaluated in the peer-reviewed literature? How is EDI presented and discussed by the wider medical community? We scanned institutional websites for physician leadership programmes, analysed peer-reviewed literature and examined material from medical education conferences. Our findings indicate that despite an apparent increase in the discussion of EDI concepts in the medical community, current physician leadership programming is built on theories that fail to move beyond race and gender as explanatory factors for a lack of diversity in physician leadership. To address inequity, physician leadership curricula should aim to equip physicians to identify and address the structural factors that perpetuate disparities.